(untitled) (Revista Contexto & Educação, 2026)
The essay problematizes the dominant paradigm of legal research oriented by a dogmatic technology, understood as an epistemic arrangement that organizes legal science around decidability. Within this horizon, collage—in dialogue with Deleuze—was mobilized to produce a defamiliarization of “legal language” and to become, within it, a “foreign native”. From this perspective, the text criticizes the capillarization of experiential technicism in legal research together with its symptoms: manualism, reverentialism, the logic of legal advisory opinions, and epistemological confusion. Drawing also on Pierre Bourdieu, it analyzes the linguistic operators that sustain the legal field’s monopoly on “pronouncing what is just,” observing the effects of neutralization, universalization, and apriorization that are inevitably reflected in knowledge production. Finally, the text outlines non-prescriptive tactics allied to the procedure of a genealogy of the self, in order to deactivate the sacrality of legal discourse and open epistemological possibilities in the field.